Ad Hoc Communication Topology Construction for Delay-Sensitive Internet of Vehicle Applications. (13th April 2022) - Lee, Joong-Lyul; Hwang, Jaejin; Park, Hyesung; Kim, Donghyun
Abstract : Advances in new technologies are changing the Internet of Things (IoTs) from vehicular ad hoc networks (VANETs) to Internet of Vehicles (IoVs). This IoV needs to construct a network topology in order to efficiently send and receive data to Cloud or Fog nodes. In such a topology construction, there are various methods of configuring a topology considering network interference and configuring a topology for energy saving, such as a mobile sensor network. However, there has been no research on the topology construction considering the rapidly high movement of mobile node, characteristic of IoV. In this article, we proposed the k -Lifetime Tree Topology Construction ( k -LTTC) algorithm during emergency situations for IoV with highly dynamic characteristics. By applying the time domain to the topology construction, it is guaranteed to maintain the topology for a specific period of time ( k -Life Time). The first algorithm is a centralized algorithm to construct k -lifetime tree topology, and the second algorithm is a decentralized algorithm to construct k -lifetime tree topology. We describe the time complexity and message complexity for the mathematical analysis of our proposed algorithms. Furthermore, we provided the simulation results to verify our proposed method.